Proceedings of the 2015 WAO Symposium on Food Allergy and the Microbiome. Issue 2 (October 2016) - Almarales, Raúl; Zamora, Mary; Tamargo, Beatriz; Averoff, Damaris; Cruz, Raysa; Diaz, Yunia; Castello, Mirta; Ciria, Alexander; Labrada, Alexis; Mateo, Maytee; Mateo, Maytee; Averoff, Damaris; et al.
Table of contents A1 Characterization of the immunoallergic profile towards the proteins of the wheat flour in Cuban population Raúl Lázaro Castro Almarales, Mary Carmen Reyes Zamora, Beatriz Tamargo, Damaris Torralba Averoff, Raysa Cruz, Yunia Oliva Diaz, Mirta Alvarez Castello, Alexander Ciria, Alexis Labrada, Maytee Mateo A2 Are peanuts causing food allergy in Cuba? Maytee Mateo, Damaris Torralba Averoff, Raysa Cruz, Yunia Oliva Diaz, Mirta Alvarez Castello, Alexander Ciria, Mary Carmen Reyes Zamora, Beatriz Tamargo, Alexis Labrada A3 Prick test and immunoallergic profile to soy allergens in Cuban population Omar Herrera, Maytee Mateo, Raysa Cruz, Mirta Alvarez Castello, Alexander Ciria, Raúl Lázaro Castro Almarales, Mary Carmen Reyes Zamora, Alexis Labrada A4 Skin sensitization and immunoallergic profile to hen's egg in Cuban population José Severino Rodríguez Canosa, Raysa Cruz, Maytee Mateo, Mirta Alvarez Castello, Alexander Ciria, Raúl Lázaro Castro Almarales, Mary Carmen Reyes Zamora, Alexis Labrada A5 Sensitization to three domestic mites in patients with adverse food events to shellfish Mirta Alvarez Castello, Raúl Lázaro Castro Almarales, Alexis Labrada, Biocen A6 Diagnostic efficacy by skin prick test with allergenic extracts of legumes in Cuban patients Yamilet Ibizate Novales, Ilonka Estruch Fajardo, Alexis Labrada, Maytee Mateo, Armando Ginard A7 Baked egg goods without wheat flour carry an increased risk of reaction Bruce Lanser, Anna Faino, Erwin Gelfand, Pia Hauk A8 Prevalence, incidence and associated risk factors of adverse reaction to food in Cuban infants - a population-based prospective study Silvia Venero Fernández, Julia Urbina, Mirta Alvarez Castello, Raúl Lázaro Castro Almarales, Ramón Suárez Medina, Hermes Fundora Hernández, John Britton, Andrew William Fogarty A9 Microbiome in ice machines and assessing the plasma nanotechnology in breaking the biofilm and improving air quality Nabarun Ghosh, Clinton Ross Bell, Chandini Revanna, Constantine Saadeh, Jeff Bennert, Danius Bouyi, Mitsy Veloz, Nelofar Sherali A10 Characteristics of patients with food allergy in health public service Magna Coelho A11 Allergic rhinitis and asthma index increased in Texas panhandle and AHPCO and plasma nanotechnology as solutions Nabarun Ghosh, Jeff Bennert, Danius Bouyi, Constantine Saadeh, Clinton Ross Bell, Mitsy Veloz, Chandini Revanna, Nelofar Sherali A12 Antigen-specific T follicular helper cells mediate peanut allergy in mice Joseph J. Dolence, Takao Kobayashi, Koji Iijima, Hirohito Kita, Hirohito Kita, Ashli Moore, James Krempski A13 Production of recombinant Mal d 3, a major apple allergen, in Pichia Pastoris, to investigate the impact of the food matrix and post-translational modifications on Mal d 3 immuno-reactivity Roberta Aina, Riccardo Asero, Sabine Pfeifer, Pawel Dubiela, Merima Bublin, Christian Radauer, Piotr Humeniuk, Karin Hoffmann-Sommergruber A14 Reaction to sports drink: no whey! Whey allergy in absence of clinical cow's milk allergy Frank Eidelman, Ves Dimov, Charl Khalil A15 Food allergy on Tumblr: focus on teenage audience may increase educational impact Ves Dimov, Frank Eidelman, Charl Khalil A16 Changes in IgE levels following one-year immunizations in two children with food allergy Alice E. W. Hoyt, Peter Heymann, Alexander Schuyler, Scott Commins, Thomas Platts-Mills A17 IgE and IgG4 antibodies to cow's milk components in children with eosinophilic esophagitis: higher specific IgG4 antibodies and IgG4:IgE ratios compared with subjects with IgE-mediated food allergy Alexander Schuyler, Patrice Kruszewski, John Russo, Lisa Workman, Thomas Platts-Mills, Elizabeth Erwin, Anubha Tripathi A18 Frequency of Sensitization to Food Allergens in Patients with Rhinitis and Asthma in the National Medical Center La Raza "Dr. Antonio Fraga Mouret", Mexico City Gabriela Yvette Castellanos, Elizabeth Mendieta, Martín Becerril-Angeles